Implementasi Tradisi Muslimatan Terhadap Spiritual Masyarakat Di Desa Sana Daja Pasean Pamekasan - Juhairiyah, Juhairiyah; Rofiki, Rofiki; Wan Mokhtar, Wan Khairul Aiman; Riadi, Ahsan (STAI Publisistik Thawalib Jakarta, 2022)
The purpose of the research is to explain the implementation of the Muslimatan tradition and its impact on the spirituality of the Sana Daja community. The research method uses a case study approach. Data collection techniques by observation, interviews, and documentation. Data processing techniques with reduction, presentation, and drawing conclusions or levers. The results showed: the implementation of the Muslim tradition with several activities including: 1) reading the Prophet's prayer, which is a chanting sholawat to praise the Prophet Muhammad SAW as a sign of affection for the Prophet 2) reading Surah Yasin, to instill Islamic aqidah and hope that good in the hereafter 3) tahlil, which contains dhikr readings whose rewards are addressed to relatives who have died 4) offering mauidzoh hasanah, which is a spiritual shower that contains religious knowledge and 5) social gathering an activity that is in tradition muslimatan to train the people of Sana Daja in saving money so that they live more prosperously. Second, the impact of the Muslim tradition on the spirituality of the community has a positive effect on 1) religion, can increase piety, submission to Allah SWT, and can know religious knowledge in detail, and become a society that has high self-awareness, 2) social, increasing ukhuwah Islamiyah, and 3. The economy makes people more prosperous in their economy.